Quantifying the Impact of Tree Species Diversity on Carbon Sequestration Insight of Two-Decade Plantation (Journal of Asian Development Studies, 2025)
Forest plantations play a crucial role in combating climate change by acting as carbon sinks and supporting carbon trading initiatives. This study investigates carbon sequestration in two age classes 4 years and 20 years of six tree species at Pakistan Forest Institute: Bombax ceiba, Dalbergia sissoo, Eucalyptus camaldulensis, Morus alba, Paulownia fortune , and Populus deltoides. Data on DBH and height were used with species-specific allometric equations to estimate above- and below-ground biomass. Eucalyptus camaldulensis showed the highest carbon sequestration, storing 1,027 kg at 20 years (0.127 tons/year) versus only 6.7 kg at 4 years. Populus deltoides also showed strong performance with 471 kg at 20 years. ANOVA and correlation analysis confirmed a strong positive association between tree size, age, and carbon accumulation (p < 0.001). The study underscores the need for species-specific planning and long-term plantation maturity to optimize sequestration outcomes. These findings have implications for afforestation and REDD+ initiatives in Pakistan, offering a scientific foundation for sustainable forest management strategies.